Study of the high rotational bands of heavy nuclei (A=190) by An approach keeping the number of particles - zohra, Hamel Fatima; Medjadi, Djamel Eddine (Journal of natural sciences, life and applied sciences, 2019)
Current study propuse to treat on first all what is mentioned the these statment which role essentially in two steps .First, we start with a presentation of the formalism of the approach HTDA (Higher Tamm Dancoff approximation).This approximation is based on the excitations particle-hole permits the conservation of a number of particles in a middle field. A special attention will be drifted on the HTDA code with triaxial symmetry that we will extend in a way that allows us to include in the Hamiltonian a rotational part to process the collective modes of rotation in the deformed nuclei. Secondly, the Cranking version of this formalism (Cr.HTDA) Will allow us to calculate the moments of inertia of the super-distorted bands of nuclei in the mass region A 190.These will be compared to the experimental data and with those of the Cranking version of the approach Hartree- Fock- Bogoliubov. This work, will offer an interesting perspectives, calling for certain ameliorations or extensions of the HTDA code.